2010
DOI: 10.1007/s11097-010-9159-x
|View full text |Cite
|
Sign up to set email alerts
|

Imagery and memory illusions

Abstract: This article provides a summary of current knowledge about memory illusions. The memory illusions described here focus on the recall of imagined events that have never actually occurred. The purpose is to review theoretical ideas and empirical evidence about the reality-monitoring processes involved in memory illusions. Reality monitoring means deciding whether the memory has been perceptually derived or been self-generated (thought or imagined). A few key findings from the literature have been reported in thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 36 publications
(37 reference statements)
1
7
0
Order By: Relevance
“…Therefore, we have to be cautious concerning the hypothesis that imaging encoding would be a good candidate for reducing every sort of false memories of events. Indeed, at the opposite, numerous studies using imaging instruction in false events induction have revealed the negative role of visual images on source recognition with an imagination inflation effect or false autobiographical memories (Goff & Roediger, 1998;Mazzoni & Memon, 2003; for a review, see Robin, 2010).…”
Section: Effect Of Visual Imagery On False Memories In Drm and Misinfmentioning
confidence: 99%
“…Therefore, we have to be cautious concerning the hypothesis that imaging encoding would be a good candidate for reducing every sort of false memories of events. Indeed, at the opposite, numerous studies using imaging instruction in false events induction have revealed the negative role of visual images on source recognition with an imagination inflation effect or false autobiographical memories (Goff & Roediger, 1998;Mazzoni & Memon, 2003; for a review, see Robin, 2010).…”
Section: Effect Of Visual Imagery On False Memories In Drm and Misinfmentioning
confidence: 99%
“…Successful methods include repeated study presentations (Benjamin, 2001; McDermott, 1996), instructional warnings presented before study and/or test (Gallo, Roediger, & McDermott, 2001; McCabe & Smith, 2002; Neuschatz, Payne, Lampinen, & Toglia, 2001), and requiring source monitoring of the origins of one’s memories at test (Johnson, Hashtroudi, & Lindsay, 1993; Multhaup & Conner, 2002; although see Hicks & Marsh, 2001, for exception). Manipulations that induce distinctive encoding of the list items have also been successful at reducing the illusion, including picture presentations (Israel & Schacter, 1997), unique fonts (Arndt & Reder, 2003), mental imagery (Bodner, Huff, Lamontagne, & Azad, 2017; Foley, Wozniak, & Gillum, 2006; Gunter, Bodner, & Azad, 2007; Oliver, Bays, & Zabrucky, 2016; Robin, 2010), pleasantness ratings (Gunter et al, 2007; Huff & Bodner, 2013), and anagram generation (Bodner et al, 2017; Gunter et al, 2007; Huff & Bodner, 2013; McCabe & Smith, 2006). Some of these distinctive manipulations, such as generation, can induce a mirror effect (Glanzer & Adams, 1990)—an increase in correct memory coupled with a decrease in false memory—relative to a read-only control task.…”
mentioning
confidence: 99%
“…For over 30 years, the issue of false memories has been the source of a growing number of studies in psychology (for a review, see Brainerd & Reyna, 2005; Gallo, 2006; 2010; Lyle & Johnson, 2007). The influence of mental images on memory illusions has been widely examined in line with the theory of source monitoring (Durso & Johnson, 1980; Johnson, Hashtroudi, & Lindsay, 1993; Johnson & Raye, 1981; Lyle & Johnson, 2006; for a review, see Robin, 2010). Source monitoring is defined as the ability to identify the origin (source) of the information recovered in the memory (Johnson, 1997).…”
mentioning
confidence: 99%